Contributions of Social Currencies to Alternative Short Food Supply Chains. Issue 1 (9th November 2017) - Rivero Santos, Ana María
Abstract : Social currencies are monetary instruments that provide networks for goods and services exchange parallel to the conventional economy in which people's needs are met using resources that are available in a territory, without requiring conventional money. Alternative short food supply chains are initiatives of grassroots innovations that reduce not only physical but relational distance between consumers and producers of any type of products. This research aims to identify the contributions of social currencies to create short food supply chains in the territories. For this, a case study is exposed: the consumption groups and community supported agriculture (CSA) of RASTRU from Asturias, northwest Spain, and its social currency Copin . Through surveys and participant observation, it is evidenced how social currencies generate proximity and trust‐based relations between consumers and producers based on inclusion and fair access to food for people.